2008
DOI: 10.1007/s11242-008-9233-9
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropy of Seismic Attenuation in Fractured Media: Theory and Ultrasonic Experiment

Abstract: This is a study on anisotropy of seismic attenuation in a transversely isotropic (TI) model, which is a long-wavelength equivalent of an isotropic medium with embedded parallel fractures. The model is based on Schoenberg's linear-slip theory. Attenuation is introduced by means of a complex-valued stiffness matrix, which includes complex-valued normal and tangential weaknesses. To study the peculiarities of seismic attenuation versus wave-propagation direction in TI media, numerical modeling was performed. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 31 publications
2
28
0
1
Order By: Relevance
“…Seismic anisotropy due to oriented cracks, microfractures, laminae, or crystal orientation leads to an associated attenuation anisotropy. In general, seismic attenuation is at a minimum when the seismic wave propagation is parallel to the primary axis of anisotropy [e.g., Best et al , 2007; Chinchinina et al , 2009].…”
Section: Seismic Theorymentioning
confidence: 99%
“…Seismic anisotropy due to oriented cracks, microfractures, laminae, or crystal orientation leads to an associated attenuation anisotropy. In general, seismic attenuation is at a minimum when the seismic wave propagation is parallel to the primary axis of anisotropy [e.g., Best et al , 2007; Chinchinina et al , 2009].…”
Section: Seismic Theorymentioning
confidence: 99%
“…We assume that fractures are vertical and parallel to each other in the simulations because subsurface natural fracture planes tend to be vertical and parallel to the maximum horizontal stress direction (Zoback, 2010). Previous numerical and experimental studies (Tadepalli et al, 1995;Fatkhan et al, 2001;Alhussain et al, 2007;Chichinina et al, 2009;Mahmoudian et al, 2012;Far et al, 2014) on models with regularly spaced fractures have demonstrated that the EMM and DFM models are equivalent when fracture spacing is sufficiently small compared with the wavelength (e.g., < λ∕10), which is the foundation for the use of EMM in fracture characterization. However, fractures are unlikely to be uniformly distributed in the earth.…”
Section: Introductionmentioning
confidence: 99%
“…If the background medium is isotropic, with elasticity components (Lamé constants) c 12 and c 55 , and the fracture set is rotationally invariant, we have Z H = Z V ≡ Z T , and the equivalent medium is TIV with a vertical symmetry axis (VTIV), whose stiffness matrix is (Schoenberg 1983; Chichinina et al 2009; Carcione et al 2012), where c 11 = c 12 + 2 c 55 , The stiffness matrix in Coates & Schoenberg (1995) is equivalent to P of eq. () considering the lossless case (= 0).…”
Section: The Equivalent Anisotropic Medium Analytical Solutionmentioning
confidence: 99%
“…To verify that the FE implementation of the fractured medium is correct, we consider the data provided by the laboratory experiments of Chichinina et al (2009). They consider an isotropic background medium defined by c 12 = 10 GPa, c 55 = 3.9 GPa ( c 11 = 17.8 GPa) and ρ= 2300 kg m −3 .…”
Section: Examplesmentioning
confidence: 99%